2008
DOI: 10.1242/jeb.018507
|View full text |Cite
|
Sign up to set email alerts
|

Induced cell proliferation in putative haematopoietic tissues of the sea star,Asterias rubens(L.)

Abstract: SUMMARYThe coelomic fluid of the echinoderm Asterias rubens possesses large populations of circulating coelomocytes. This study aimed to expand the knowledge about the haematopoietic sources of these cells. Injection of the immune-stimulating molecules lipopolysaccharide (LPS) and concanavalin A (ConA) resulted in an increase in coelomocytes. To investigate if these molecules induce cell proliferation in putative haematopoietic tissues (HPTs), short-term exposure of the substitute nucleotide 5-bromo-2Ј-deoxyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…This study showed for the first time that proliferation of cells in distant organs, considered HPTs of sea stars (Holm et al, 2008), responded to arm regeneration and most significantly so in the coelomic epithelium. For the first time, we have also shown increased proliferation in a subpopulation of cells in distant pyloric caeca.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This study showed for the first time that proliferation of cells in distant organs, considered HPTs of sea stars (Holm et al, 2008), responded to arm regeneration and most significantly so in the coelomic epithelium. For the first time, we have also shown increased proliferation in a subpopulation of cells in distant pyloric caeca.…”
Section: Discussionmentioning
confidence: 75%
“…When investigating other areas of the sea star, however, it was found that the coelomic epithelium, axial organ (Leclerc et al,'87), and Tiedemann body all responded with increased cell proliferation (Holm et al, 2008;Oweson et al, 2008). This result strongly suggests these organs to be progenitor tissues for the circulating coelomocytes, as had been speculated earlier (Bossche and Jangoux, '76;Kaneshiro and Karp, '80;Muñ oz-Chápuli et al, 2005).…”
mentioning
confidence: 76%
See 3 more Smart Citations